2023
DOI: 10.2174/1389557523666230125104753
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Agmatine Neurotransmission in Acute and Chronic Stressrelated Conditions

Abstract: Adaptive responses to stressful stimuli in the environment are believed to restore homeostasis after stressful events. Stress activates the hypothalamic-pituitary-adrenocortical (HPA) axis, which releases glucocorticoids (GCs) into the bloodstream. Recently, agmatine, an endogenous monoamine, was discovered to have the potential as a pharmacotherapy for stress. Agmatine is released in response to certain stress conditions, especially those involving GCs, and participates in establishing homeostasis disturbed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 126 publications
2
3
0
Order By: Relevance
“…Considering that several previous studies have indicated that PS might differentially affect each sex (Gué et al., 2004; GhotbiRavandi et al., 2021), the sex‐dependent effects of PS must be taken into account. The findings of our present study are comparable to our recent findings in female offspring (Hassanshahi et al., 2023). Similar to what we observed in the male offspring, PS resulted in impaired locomotor activity, increased anxiety‐like behavior, heightened drug‐seeking behavior, and impaired passive avoidance memory in the female offspring, which were prevented with the administration of agmatine during the pregnancy (Hassanshahi et al., 2023).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Considering that several previous studies have indicated that PS might differentially affect each sex (Gué et al., 2004; GhotbiRavandi et al., 2021), the sex‐dependent effects of PS must be taken into account. The findings of our present study are comparable to our recent findings in female offspring (Hassanshahi et al., 2023). Similar to what we observed in the male offspring, PS resulted in impaired locomotor activity, increased anxiety‐like behavior, heightened drug‐seeking behavior, and impaired passive avoidance memory in the female offspring, which were prevented with the administration of agmatine during the pregnancy (Hassanshahi et al., 2023).…”
Section: Discussionsupporting
confidence: 93%
“…The findings of our present study are comparable to our recent findings in female offspring (Hassanshahi et al., 2023). Similar to what we observed in the male offspring, PS resulted in impaired locomotor activity, increased anxiety‐like behavior, heightened drug‐seeking behavior, and impaired passive avoidance memory in the female offspring, which were prevented with the administration of agmatine during the pregnancy (Hassanshahi et al., 2023). Moreover, our findings indicate that PS had no detrimental effects on hippocampal BDNF both in male and female offsprings.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, it has been reported that agmatine possesses antidepressive (Neis et al, 2016), anxiolytic (Gawali et al, 2017), antinociceptive (Kotagale et al, 2013) and anti‐inflammatory (Kim et al, 2016) properties. Agmatine has also proven to be a protective agent against chronic unpredictable stress‐induced behavioural and cognitive deficits (Gawali et al, 2017; Taksande et al, 2013), which involved inhibition of NMDA receptors as well as activation of BDNF signalling (Gawali et al, 2017; Hassanshahi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Agmatine binds with high affinity to α2-adrenoceptors and imidazoline binding sites, as well as being an antagonist of the N-methyl-D-aspartate (NMDA) receptor and a competitive inhibitor of nitric oxide synthase (NOS) (Gawali et al, 2017). Studies have revealed that agmatine is implicated in the physiological response to stress as well as its associated disorders (for review, see Hassanshahi et al, 2023). Following investigations of effects of agmatine in various neurological and neuropsychiatric disorders, evidence has emerged suggesting a potential of agmatine as a neuroprotective agent.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of GCSs on mediators of inflammation and immune responses include: (i) reducing the production of prostaglandin compounds by decreasing the expression of cyclooxygenase II and inhibiting the release of arachidonic acid substrates [ 153 ]; (ii) decreasing the production of numerous cytokines, including TNF-α, cell adhesion molecules, IL-1, IL-3, IL-2, IL-4, IL-6, IL-5, IL-8, and granulocyte-macrophage colony-stimulating factor, largely secondary to the inhibition of gene transcription [ 154 ]; (iii) lowering the concentration of complement components in plasma [ 155 ]; (iv) reducing the production of NO by inducing the production of nitric oxide synthase 2 (NOS2) isoforms [ 156 ]; (v) decreasing the release of histamine and other mediators from basophils and mast cells [ 157 ]; (vi) reducing the production of immunoglobulin G (IgG) [ 158 ]; (vii) increasing the synthesis of anti-inflammatory factors such as IL-10, IL-1 soluble receptor, and clusterin [ 159 ]; (viii) endogenous GCs entering the bloodstream increase in quantity during inflammation and stress events [ 160 ], playing a crucial regulatory role in preventing excessive activation of inflammation and other potent defense responses, which, if left uncontrolled, may lead to a state of dysregulation in the organism [ 161 ].…”
Section: Mechanistic Pathways Of Gc Action In Tumor Cellsmentioning
confidence: 99%